Optimal design of conductive natural branched pathways for cooling a heat‐generating volume. Issue 3 (9th November 2020) - Li, Yinglin; Feng, Mengli
Abstract: The application of constructal networks to cool a heat‐generating volume has been the subject of many research studies in the past decade. However, the current volume‐point constructs mainly include rectangular, triangular, and parabolic‐shaped constructs, and none of them are similar to the constructs of common plant leaves in nature. A bionic quadrilateral volume based on the shape of common leaf veins is proposed, and the heat‐conductive model of the quadrilateral volume is established. The analysis results show that the minimal peak temperature difference can be as low as 1.3 k when the porosity α 1 of the quadrilateral volume is equal to 0.15; the recommended value of interval number n of central link is 30, the optimal value of exponent m 1 of the width of central link is about 0.9; and the optimal value of the aspect ratio H 1 / L 1 remains nearly constant at 0.7. When the quadrilateral volume obtains highest heat conductivity, the branching cooling links should be perpendicular to the central link.